2016
DOI: 10.12688/f1000research.9100.1
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative regional anaesthesia and postoperative longer-term outcomes

Abstract: Regional anaesthesia provides effective anaesthesia and analgesia in the perioperative setting. Central neuraxial blocks—that is, spinal and epidural blocks—are well established as an alternative or adjunct to general anaesthesia. Peripheral blocks may be used as part of multimodal anaesthesia/analgesia in perioperative practice, reducing the need for opioid analgesics and enhancing early recovery. Furthermore, regional anaesthesia has increased in popularity and may be done with improved ease and safety with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 52 publications
0
14
0
3
Order By: Relevance
“…Epidural anesthesia is undoubtedly the most effective form of pain relief and reduces opioid consumption. 86 A recent meta-analysis concluded that epidural in addition to GA reduced both postoperative mortality and morbidity; however, there were higher rates of hypotension and urinary retention and a technical failure rate of 6.1%. 87 The mean age of the participants in the 125 trials included in this meta-analysis was not reported, and it is likely that they represent the general population undergoing surgery, which may benefit less from regional anesthesia than those who are frail.…”
Section: Frailty Interventionsmentioning
confidence: 99%
“…Epidural anesthesia is undoubtedly the most effective form of pain relief and reduces opioid consumption. 86 A recent meta-analysis concluded that epidural in addition to GA reduced both postoperative mortality and morbidity; however, there were higher rates of hypotension and urinary retention and a technical failure rate of 6.1%. 87 The mean age of the participants in the 125 trials included in this meta-analysis was not reported, and it is likely that they represent the general population undergoing surgery, which may benefit less from regional anesthesia than those who are frail.…”
Section: Frailty Interventionsmentioning
confidence: 99%
“…The application of local anaesthetics in the wound area, site for incision, or as a peripheral block, is a basic part of the multi-modal analgesia concept. The effects of peripheral block on early pain, reducing the need for opioid analgesics are well-known 16 . The effects beyond the early period and the duration of the pharmacological local block is less well documented 17 .…”
Section: Discussionmentioning
confidence: 99%
“…На швидкість відновлення після цього втручання, окрім ортопедичних чинників, впливає мотивація й адекватний контроль болю [3]. Регіональна анестезія забезпечує ефективне знеболювання в периопераційному періоді [9,10]. Центральні нейроаксіальні блоки, тобто спінальні та епідуральні, добре зарекомендували себе як альтернатива або доповнення до загальної анестезії.…”
Section: результати та їх обговоренняunclassified
“…Наслідки такого знеболювання щодо довгострокових результатів, таких як захворюваність, смертність і можливість прискорення відновлення в післяопераційному періоді, залишаються менш зрозумілими. Таким чином, як і раніше відсутні надійні дані про клінічний вплив регіональної анестезії за межами її добре відомих позитивних ефектів зменшення болю та скорочення споживання опіоїдів [7,9,10,12].…”
Section: результати та їх обговоренняunclassified